Development of software-based vendor independent WLAN controller. (23rd May 2019) - Ertürk, Mehmet Ali; Vollero, Luca; Aydın, Muhammed Ali
Wireless hotspots have become popular, due to their ability to provide inexpensive and easy-to-deploy network infrastructures. Controlling and maintaining large-scale wireless infrastructures with traditional methods is complex and error-prone. Hence, it is necessary to use centralised solutions to handle configuration, monitoring and management functions in large-scale wireless hotspots. Existing solutions solve these problems within their hardware ecosystems and are constrained by vendor being depended on hardware and software restrictions. In this study, we propose and evaluate a wireless local area network (WLAN) access point (AP) controller built on top of a standard WLAN management protocol and free of any particular hardware and software restrictions. The proposed WLAN controller is a software component based on the control and provisioning of wireless access points (CAPWAPs) protocol. The proposed controller is evaluated by means of a TestBed including a variety of WiFi devices from different vendors to solve a QoS-LB problem.